Cost-Effectiveness of Left Ventricular Assist Devices in Ambulatory Patients With Advanced Heart Failure - Baras Shreibati, Jacqueline; Goldhaber-Fiebert, Jeremy D.; Banerjee, Dipanjan; Owens, Douglas K.; Hlatky, Mark A. (JACC. Heart failure, 2017)
This study assessed the cost-effectiveness of left ventricular assist devices (LVADs) as destination therapy in ambulatory patients with advanced heart failure. LVADs improve survival and quality of life in inotrope-dependent heart failure, but data are limited as to their value in less severely ill patients. We determined costs of care among Medicare beneficiaries before and after LVAD implantation from 2009 to 2010. We used these costs and efficacy data from published studies in a Markov model to project the incremental cost-effectiveness ratio (ICER) of destination LVAD therapy compared with that of medical management. We discounted costs and benefits at 3% annually and report costs as 2016 U.S. dollars. The mean cost of LVAD implantation was $175,420. The mean cost of readmission was lower before LVAD than after ($12,377 vs. $19,465, respectively; p < 0.001), while monthly outpatient costs were similar ($3,364 vs. $2,974, respectively; p = 0.54). In the lifetime simulation model, LVAD increased quality-adjusted life-years (QALYs) (4.41 vs. 2.67, respectively), readmissions (13.03 vs. 6.35, respectively), and costs ($726,200 vs. $361,800, respectively) compared with medical management, yielding an ICER of $209,400 per QALY gained and $597,400 per life-year gained. These results were sensitive to LVAD readmission rates and outpatient care costs; the ICER would be $86,900 if these parameters were 50% lower. LVADs in non–inotrope-dependent heart failure patients improved quality of life but substantially increased lifetime costs because of frequent readmissions and costly follow-up care. LVADs may provide good value if outpatient costs and adverse events can be reduced. [Display omitted]